Sustainable bionic soil and preparation method and application thereof
By using bionic soil curing agent prepared by coal-based solid waste and cement and other materials combined with polyacrylamide to modify the in-situ soil, the environmental risks and soil structure damage problems of traditional coal gangue reclamation methods are solved, and coal is realized Effective disposal of gangue and improvement of soil performance.
Patent Information
- Application Number
- CN202411480379.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional coal gangue reclamation methods have problems such as high environmental risks, heavy metal leaching, and soil structure damage, making it difficult to effectively deal with the large amount of coal gangue production and environmental impact.
The biomimetic soil curing agent is prepared using coal-based solid waste and cement and other materials. By using it in combination with polyacrylamide (PAM), the in-situ soil is modified to form a new type of sustainable biomimetic soil, which is used to build a deep layer with coal gangue. Soil layer to improve soil geo-performance, flame retardant capacity and heavy metal curing effect.
It has achieved in-situ large-scale disposal and resource utilization of coal gangue, reduced environmental risks, improved the soil's geotechnical properties and heavy metal curing capabilities, and ensured the soil's water retention and water migration functions.
Smart Images

Figure CN119430753A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of soil improvement, and in particular, relates to sustainable bionic soil and a preparation method and application thereof. Background Art
[0002] The in-situ large-scale disposal of coal gangue has always been one of the difficult problems in the process of coal mining and processing. According to statistics, in 2022, my country's raw coal production accounted for about 51.8% of the global coal production, which was 4.56 billion tons, of which the output of coal gangue was about 684 million tons. As of now, my country's cumulative coal gangue stock is about 6 billion tons, and the accumulation of untreated coal gangue will cause serious environmental problems. For example, the enrichment of heavy metals in coal gangue caused by long-term accumulation and leaching will increase the health risks of humans and animals, the spontaneous combustion of coal gangue will cause air pollution, and the landslide and other engineering geological disasters caused by the instability of unsaturated coal gangue mountains. At present, the utilization technology of coal gangue is mainly concentrated in: co-combustion with coal for power generation, preparation of building and roadbed materials, new chemical materials and extraction of high value-added metals. These solutions have sufficient market prospects in the economically developed eastern region of my country, but are not suitable for the remote northwestern region with larger coal gangue production and smaller demand for building materials. Although the existing coal mining technology has made a series of optimizations for the filling of coal gangue at the bottom of the well, the existing problems include limited consumption of gangue, affecting the efficiency of the coal mining process, and failing to solve the fundamental problem of large output of coal gangue. Therefore, it is urgent to develop technology for the in-situ large-scale utilization of coal gangue.
[0003] Land reclamation is one of the best options for large-scale in-situ disposal of coal gangue. The main method is to lay a low-permeability bottom impermeable layer before the landfill of coal gangue, or to cover the surface of the yard with soil to isolate the coal gangue. This method has achieved good results. However, the traditional landfill method does not take into account the diffusion and transportation of the overall material of coal gangue and the outside world. After a long storage time (such as decades), the environmental risk is prominent. The main reasons are: first, there are still a large number of pores inside the coal gangue, and long-term accumulation and heat generation are very easy to spontaneously combust; second, the damage of the impermeable layer or insufficient covering soil during the reclamation process leads to the leaching of heavy metals such as Pb and As in the coal gangue; third, the soil layer after reclamation lacks the structural layer of natural soil, and loses the water migration and supply function that the natural soil layer should have. In view of the functional characteristics of coal gangue such as inert materials, and its chemical composition similar to that of natural rock formations (both are mainly SiO2 and Al2O3), it can be considered as an inert rock component for soil reconstruction. The actual engineering requirements for coal gangue reclamation do not allow for secondary crushing and reprocessing. Therefore, the present invention proposes to first fill coal gangue and then grout bionic soil to complete the "bionic soil-coal gangue" deep soil construction. Bionic soil should be able to improve the geotechnical properties of in-situ soil, and should also have the ability to flame retard and solidify heavy metal precipitation.
[0004] The present invention aims at the problem of high ecological risk of traditional coal gangue reclamation and covering soil, and proposes to prepare bionic soil curing agent with coal-based solid waste in mining area as raw material, and modify the in-situ soil to achieve the best geotechnical, environmental and water transport functions. Studies have shown that high-strength cementitious materials can be prepared by synergistic effect of the chemical and mineralogical properties of Portland cement (PO) and coal-based solid waste (such as fly ash, desulfurized gypsum); its potential hydration products include hydrated calcium silicate (CSH) and calcium aluminate (AFt), etc., which can fill the pores of soil to improve the pore structure of soil and improve the mechanical properties, and also have very good adsorption, encapsulation and ion exchange effects on heavy metals. Polyacrylamide PAM is a typical highly absorbent polymer. Due to the hydrophilic groups such as -OH, -COOH and -CONH on its molecular surface, it can not only promote the formation of soil aggregates, but also improve the heavy metal adsorption capacity of soil. It has achieved good results in the engineering application of constructing soil-cement underground barriers. Therefore, there is great potential for in-situ soil modified by multiple admixtures to be used together with gangue to construct a new deep soil layer. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a sustainable bionic soil and its preparation method and application. The sustainable bionic soil of the present invention provides an effective solution for the in-situ large-scale disposal and resource utilization of coal gangue.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0007] One aspect of the present invention provides a sustainable bionic soil, which comprises, by weight percentage, silt and a curing agent, wherein the curing agent is 6-8% of the mass of the silt; the curing agent comprises a curing agent I and a curing agent II, wherein the curing agent II is 0-1‰ of the mass of the silt.
[0008] In a preferred embodiment of the present invention, the curing agent I comprises: cement, fly ash and desulfurized gypsum; the mass ratio of the cement, fly ash and desulfurized gypsum is (10-12): (6-10): (1-5).
[0009] In a preferred embodiment of the present invention, the curing agent II is polyacrylamide, and the molecular weight of the polyacrylamide is between 10 and 20 million.
[0010] Another aspect of the present invention also provides a method for preparing the sustainable bionic soil as described above, the method comprising the following steps:
[0011] S1: preparing curing agent I: drying cement, fly ash and desulfurized gypsum and mixing them evenly according to the proportion;
[0012] Prepare curing agent II: polyacrylamide, molecular weight of 10 to 20 million;
[0013] S2: Preparation of bionic soil: First, dissolve curing agent II in water to obtain an aqueous solution of curing agent II, then add silt and curing agent I in sequence, stir evenly to obtain a mixture, and subject the obtained mixture to injection molding, curing and demolding in sequence to obtain a sustainable bionic soil product.
[0014] In a preferred embodiment of the present invention, in step S1, the drying conditions are: 80-120° C., time 1-3 h.
[0015] In a preferred embodiment of the present invention, in step S1, the curing agent II is polyacrylamide, and the molecular weight of the polyacrylamide is between 10 and 20 million.
[0016] In a preferred embodiment of the present invention, in step S2, the water is added in an amount with a mass ratio of 1:2 to the silt.
[0017] In a preferred embodiment of the present invention, in step S2, the stirring conditions are: rotation speed 57-67 r / min, time 5-15 min.
[0018] In a preferred embodiment of the present invention, in step S2, the curing process is: first curing under natural conditions for 20 to 26 hours, and then curing at a temperature of 18 to 22° C. and a humidity of 94 to 96%.
[0019] Another aspect of the present invention provides an application of the sustainable bionic soil as described above in the resource reclamation of coal gangue.
[0020] By means of the above technical solution, the present invention has at least the following advantages:
[0021] The present invention uses coal-based solid waste and cement as raw materials to prepare a new type of inorganic curing agent ISA, and at the same time studies the effect of different dosages of the curing agent ISA and curing agent II polyacrylamide PAM on the environmental characteristics of bionic soil. The soil geotechnical, ecological and environmental performance evaluation was completed by designing soil evaporation experiments, soil-water characteristic curve tests and soil heavy metal leaching experiments. The structure of the bionic soil after curing with curing agent ISA and curing agent II was characterized by MIP, TG-DSC, XRD and SEM-EDS. The results show that the addition of curing agent ISA significantly improves the geotechnical properties of the in-situ soil, such as unconfined compressive strength and specific gravity. The particle size analysis suggests that curing agent ISA increases the proportion of soil clay and powder particles. The results of soil water characteristic experiments, water evaporation experiments and mercury injection experiments show that the dosage of curing agent ISA can maintain the bimodal structure of the soil while ensuring good water retention capacity.
[0022] The sustainable bionic soil obtained according to the present invention has a good solidification and stabilization effect on heavy metals Pb, Zn, Cu and As. The PAM particles of the curing agent II and the hydration product of the curing agent ISA can not only fill the soil pores and improve the soil strength, but also complete the adsorption, encapsulation and fixation of heavy metals. The sustainable bionic soil prepared by the present invention provides an effective solution for the in-situ large-scale disposal and resource utilization of coal gangue in the northwest mining area of my country.
[0023] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a flow chart for preparing the sustainable bionic soil;
[0025] Figure 2 Changes in soil properties under different ISA dosages and curing times: a) UCS; b) pH; c) EC; d) relationship between pH and UCS; e) relationship between EC and UCS (repetitions = 3, COV < 5.0%);
[0026] Figure 3 The moisture characteristic curves of bionic soil with different contents;
[0027] Figure 4 The distribution law of soil moisture content during evaporation: a) lateral distribution; b) longitudinal distribution;
[0028] Figure 5 The effect of pH on the leaching concentration of heavy metals: (a) As; b) Cu (repetition number = 3, COV < 5.0%);
[0029] Figure 6 The pore size distribution and Gaussian fitting curve of bionic soil: (a) mercury intrusion curve; (b) pore distribution curve; (c) 6% bionic soil PSD; (d) 10% bionic soil PSD (curing time 28 days);
[0030] Figure 7 Microstructure of bionic soil: (a) SEM (1μm) of bionic soil with different ISA dosages; (b) XRD patterns of in-situ soil and 6% bionic soil at 14d and 28d; (c) EDS element distribution of 6% soil particles (curing time 28d);
[0031] Figure 8 The microstructure of bionic soil: (a) TG of bionic soil with different ISA dosages; (b) DSC curves of 6% and 10% bionic soil;
[0032] Fig. 9Schematic diagram of the bionic soil-coal gangue solidification stabilization mechanism and the improvement of water transport performance of the reconstructed soil layer. DETAILED DESCRIPTION
[0033] In order to make the technical means, creative features, objectives and effects of the present invention easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods.
[0035] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0036] Unless otherwise specified, the soil used in the following examples was collected from a coal mining subsidence area in Ordos City, Inner Mongolia (north latitude, east longitude). The soil sample collection and sample processing refer to the "Technical Specifications for Soil Environmental Monitoring" (HJ / T 166-2004). After air drying for 48 hours, the soil was screened with 2 mm and tested to determine the basic properties of the soil; the gangue was collected from a yard in the Bulianta mining area of Ordos. The in-situ gangue and soil index tests are shown in Table 1.
[0037] Table 1 Basic properties of in-situ soil and coal gangue
[0038]
[0039]
[0040] Note: In the table a The number of replicates was 3, and the coefficient of variance (COV) was <5.0%; b Soil particle size testing and analysis were performed using Mastersizer 2000.
[0041] Unless otherwise specified, the composition and physical and chemical properties of the raw materials used in the following examples are shown in Table 2:
[0042] Table 2 Chemical composition of soil, cement, fly ash, desulfurized gypsum and PAM
[0043]
[0044] Example 1: Preparation of curing agent and sustainable bionic soil
[0045] 1. Composition and preparation of curing agent
[0046] (1) Composition of curing agent: The curing agent of this embodiment is composed of two parts: curing agent I and curing agent II. Among them:
[0047] Solidifying agent I is an inorganic solidification agent (hereinafter referred to as ISA), the main components of which are cement (benchmark cement PO 42.5), fly ash and desulfurized gypsum (obtained from a coal preparation plant in Ordos).
[0048] Curing agent II is a polymer curing agent: anionic PAM with a molecular weight of 15 million. The composition and physical and chemical properties of curing agent I and curing agent II are shown in Table 2.
[0049] Based on the preliminary experimental results, the mass ratio of cement, fly ash and desulfurized gypsum in the curing agent ISA in the sustainable bionic soil is 12:8:3; the PAM dosage is 0.5‰ of the total amount of silt.
[0050] (2) Preparation of curing agent I: Cement, fly ash and desulfurized gypsum were dried at 105° C. for 2 h, corresponding proportions were weighed, and the mixture was thoroughly mixed to obtain curing agent I.
[0051] Since the ISA dosage has a great influence on the geotechnical properties, this paper only discusses the experimental results under different ISA dosage optimization.
[0052] 2. Composition and preparation of sustainable bionic soil
[0053] Figure 1 The preparation process of the sustainable bionic soil of the present invention is shown in FIG. The preparation process of the sustainable bionic soil of this embodiment includes:
[0054] First, dry the in-situ soil for 12 hours and then pass it through a 2 mm sieve to obtain silt for later use.
[0055] Then, the curing agent ISA prepared in Example 1 was mixed with silt in proportions of 2%, 4%, 6%, 8% and 10% respectively according to a preset ratio, and the amount of deionized water was calculated based on a water-to-solid ratio of 0.5 (the moisture content value was greater than the liquid limit of the silt to ensure that the soil had fluidity).
[0056] Based on the fact that the in-situ soil is free of heavy metal pollution, and considering that the actual use scenario is the evaluation of the solidification effect of modified bionic soil on heavy metals in coal gangue, in this embodiment, four typical heavy metals with ecological risks in coal gangue, Zn, Pb, As and Cu, are selected as the objects, and combined with the total value of the content of heavy metal forms other than the residual state, the specific operation is: dissolving the exogenous heavy metals in deionized water to prepare a simulated exogenous heavy metal solution containing Zn, Pb, As and Cu; dissolving PAM in deionized water to obtain a PAM aqueous solution; according to the liquid-solid mass ratio of 1:2, the obtained simulated exogenous heavy metal solution, PAM aqueous solution, silt and curing agent ISA are placed in a stirring pot, and slowly stirred at 62±5r / min for 10 minutes to make it uniform, and obtain a soil mixture. Among them, the contents of each heavy metal in the soil mixture are: Zn 50mg / kg, Pb 20mg / kg, As 2.5mg / kg and Cu30mg / kg.
[0057] The obtained soil mixture was then transferred to a circular mold (Φ50mm×H 100mm), and an oscillator was used to remove bubbles and the surface was scraped to complete the preparation. After curing for 24 hours under natural conditions, the mixture was demoulded and sealed in a polyethylene bag, and transferred to a standard curing box (temperature 20±2℃, relative humidity 95%) for curing until the target time. Each bionic soil column was tested in triplicate, and the following UCS (saturated unconfined compressive strength), pH and EC (soil electrical conductivity) and leaching experiments were completed respectively.
[0058] Soil evaporation experiment soil column: Customized polyethylene soil column with a height of 120cm and an inner diameter of 10cm. Four sampling observation ports with a diameter of 4cm are reserved every 20cm from top to bottom of the soil column for sampling and testing soil moisture. 20cm high dry quartz sand that has passed through a 60-80 mesh sieve is filled at the bottom of the soil column, and then the newly mixed slurry bionic soil is filled into the soil column. Every 2cm high soil sample is filled, the side wall of the column is knocked to remove bubbles to ensure that there is no stratification in the column. A total of 6 soil columns (ISA dosage 0%, 2%, 4%, 6%, 8% and 10%) are set up and left to stand for 12 hours after filling. The SL-100 soil moisture sensor is used at each soil column observation port to monitor the moisture content and conductivity in real time, and the recording period is 60 days.
[0059] Table 3 below summarizes the sustainable bionic soil and corresponding test items obtained under different curing agent ISA dosages, injection mold sizes, and curing times. When the soil column sample reaches the target curing time, it is immediately taken out, and the strain rate is controlled to 1% / min in accordance with the ASTM D421 standard to complete the UCS test of a group of 3 samples. Then take 10g of soil sample from the broken UCS sample, and complete the pH, EC and heavy metal tests in accordance with GB / T 50123-2019. The soil pH uses a Mettler Toledo FE48 pH meter, and the instrument used for the EC test is the Leiji DJS-10.
[0060] Table 3 ISA dosage, curing time and test items in bionic soil
[0061]
[0062]
[0063] Table 4 shows the physical properties of soil samples after 28 days of curing with different dosages of ISA bionic soil curing agent. Compared with the in-situ soil, with the increase of the dosage of ISA curing agent, the liquid limit and plastic limit of the soil showed a downward trend, and the specific gravity increased slightly: the plasticity index of the soil with 6% and 10% dosage decreased to 15.01 and 14.28, respectively, and the specific gravity was 2.72-2.74. The pH of the soil increased with the increase of the dosage of curing agent, from 9.72 to 11.12. In actual use scenarios, too high pH is not conducive to the restoration of soil ecological functions, so the dosage of bionic soil curing agent needs to be strictly controlled. The particle size analysis results show that the dosage of curing agent ISA significantly reduces the proportion of sand particles in the soil and increases the proportion of clay particles and silt particles. For example, compared with the in-situ soil, the proportion of sand particles in the 6% bionic soil decreased from 69.48% to 48.86%, while the proportion of clay and silt particles increased from 1.5% and 28.94% to 2.78% and 48.36%.
[0064] Table 4 Main physical and chemical parameters of bionic soil with different curing agent ISA ratios
[0065]
[0066] Figure 2 The change patterns of UCS, pH and EC of bionic soil with different ISA dosage and curing age are shown. All data were tested 3 times and the average value was plotted in the figure to ensure the repeatability of the test results (the coefficient of variation was less than 5.0%). Figure 2It can be seen that the dosage of curing agent ISA and the curing time are positively correlated with the UCS value of bionic soil, and the strength development characteristics are almost the same as those of cement and slag solidified soil. This is mainly because the cement (C2S, C3S), fly ash, and desulfurized gypsum in the curing agent ISA react with the soil matrix at the same time to react with hydration and volcanic ash, and the additional products such as hydrated calcium silicate (CSH), hydrated calcium aluminosilicate (CASH) and ettringite (AFt) are inserted into the soil particles, filling the soil pores and increasing the soil aggregate particles. At the same time, the addition of PAM will also affect the development of the uniaxial compressive strength of the soil, generating micropores in the early stage of soil consolidation (7d, 14d), resulting in structural instability, slow strength development or even reduction (for example, the 14d strength is lower than the 7d strength at 4% dosage); with the consumption of free water in the soil and the completion of hydration reaction after 28d, the strength is basically stable and reaches a steady state. USEPA recommends that the minimum UCS value for solidified / stabilized materials disposed in landfills is 350 kPa. To achieve this standard recommended value, 6% ISA (60 days) or 8% ISA (14 days of solidification) can be selected to prepare bionic soil.
[0067] In the early stage of the newly mixed bionic soil, the alkaline components such as Ca(OH)2 and C2S in the solidifying agent ISA dissolved, resulting in a significant increase in the soil pH value in the early stage ( Figure 2 b) As the curing time increases, the SiO2 and active alumina components in the soil matrix undergo a volcanic ash reaction, as well as a precipitation reaction containing heavy metal oxides, causing the pH to gradually decrease and stabilize (OH - The more ISA is used, the higher the soil pH value is. When the alkalinity is greater than 9.5, it can inhibit the metabolic activity of microorganisms and prevent microbial metabolism from destroying soil stability. The experimental results show that the requirement can be met when the amount of solidifying agent is greater than 6%. At the same time, the change pattern of soil EC value is almost the same as pH ( Figure 2 c) As the curing time increases, the salt content in the soil decreases significantly. As the amount of ISA increases, the salt fluctuation in the soil increases, which may be related to the more complete hydration reaction and precipitation reaction caused by increasing the amount of curing agent.
[0068] Soil pH and EC are often used as indicators for rapid evaluation of soil strength because they are simple, economical and quick to test. Figure 2 dIt can be seen that the pH and UCS of bionic soil have a significant correlation: for the same amount of curing agent, as the age increases, as the pH of the bionic soil decreases, the UCS gradually increases. For the bionic soil of the same curing age, taking the 28-day age as an example, the lower the curing agent dosage, the lower the pH, but the corresponding UCS will also be lower. This is because the soil minerals gradually adsorb heavy metals Pb and Zn and react with OH in the pore water. -The precipitation reaction occurs, and the generated hydroxide precipitate and AFt fill the in-situ soil pores and increase the contact points between soil particles. - is gradually consumed, the pH value is lowered, and the soil strength is improved. Figure 2 e It can be seen that with the increase of curing age of bionic soil, UCS and EC show a negative correlation. It can be seen that with the accumulation of reaction products in bionic soil, soluble salts are consumed and the conductivity decreases significantly (<1000μS / cm).
[0069] Example 2: Soil-Water Characteristic Curve (SWCC) Test of Different Sustainable Bionic Soils
[0070] Take different dosages of ISA (0%, 2%, 4%, 6%, 8% and 10%) and silt, mix them evenly and put them into a ring cutter with a height of 5 cm and an inner diameter of 8 cm (see Table 3). Immerse the ring cutter in deionized water for 60 minutes and take it out after the soil sample is fully saturated and wet. Insert two tensiometers (the soil head of the catheter has been fully wetted) into the two holes on the side of the ring cutter and place them on an electronic scale. Record the data changes of soil volume moisture content and soil suction value under simulated sunlight. When the water in the tensiometer is completely lost, the evaporation experiment is terminated and the soil moisture content at this time is determined. Through the changes in the moisture characteristic parameters and unsaturated hydraulic conductivity of the freshly mixed bionic soil, the changes in the water holding capacity of the freshly mixed bionic soil caused by different dosages of ISA can be quantitatively analyzed. The soil hydraulic parameters are fitted using the van Genuchten model according to the following formulas (1)(2)(3):
[0071]
[0072] Where, θ: soil moisture content, %; θr: retained soil moisture content, %; θs: saturated moisture content, %; α: inverse of soil air suction value, dimensionless; h: soil suction, KPa; n, m: soil shape coefficient, dimensionless; η: effective moisture content, %; K: unsaturated hydraulic conductivity, cm·min -1 ; Ks: saturated hydraulic conductivity, cm·min -1 .
[0073] The soil-water characteristic curve (SWCC) reflects the basic characteristics of soil physical and mechanical properties. In order to ensure good fluidity, the newly mixed bionic soil needs to maintain a high water content. The change in soil water content during the consolidation process is of great significance to the later stable soil state. In order to analyze in detail the effect of different ISA application rates on soil water holding capacity, the soil suction is divided into the capillary action zone (0-100KPa) and the water film adsorption zone (>100KPa) in combination with McQueen's conceptual model. The area with soil moisture content below 10% is the low residual moisture content zone.
[0074] Figure 3 The bionic soil SWCC with different ISA contents was shown. The main migration process of soil moisture was completed in the capillary action zone. The addition of ISA increased the residual moisture content of the soil. In the initial stage of evaporation of saturated soil (soil water content>30%), the higher the ISA content, the greater the soil suction, and Ks increased from 14.488cm·min -1 Reduced to 0.108cm·min -1 , the α value is from 13.52×10 -3 Reduced to 4.027×10 -3 (Table 5); With the continuous evaporation of soil moisture, the residual moisture content of the soil tends to be stable. The θr of the in-situ soil is 5.13%. When the ISA dosage reaches 6%, the soil θr reaches a maximum value of 20.41%. Subsequently, as the application amount of the curing agent increases to 8% and 10%, the soil θr decreases to 17.61% and 4.71%, respectively, indicating that the soil has formed a dense structure, which is not conducive to the continuous retention of moisture.
[0075] Table 5 Fitting parameters of soil-water characteristic curve of freshly mixed bionic soil
[0076]
[0077] Example 3: Evaporation and migration of water in different sustainable bionic soils
[0078] The soil moisture content in the newly mixed slurry bionic soil is in an oversaturated state. After the soil column is filled and left to stand for 12 hours, the soil matrix potential and gravity potential tend to be balanced. Based on this, the soil profile moisture monitoring under the 60-day evaporation experiment was completed. The results are shown in Figure 4 .
[0079] Figure 4a It can be seen that as the evaporation time progresses, the moisture content of all soil columns decreases without groundwater recharge. Overall, the moisture content of the in-situ soil (0% dosage) profile is lower than that of all modified test groups. The application of PAM increases the soil water retention capacity, which is consistent with the results of previous studies using SAPs as soil conditioners to increase soil water retention. The moisture content distribution of each soil layer in the 2% and 4% soil columns fluctuates the most, and the overall moisture content order is 80cm>60cm>40cm>20cm. It can be seen that gravity is the main factor affecting soil water distribution. The addition of a small amount of ISA solidifier does not improve the soil water retention, but accelerates soil water loss due to the formation of non-water-stable soil aggregates. The moisture content of each soil layer in the 6% soil column is relatively stable, and the distribution pattern of its total moisture is similar to that of the original soil. The 40-60cm soil layer is the main water-retaining layer, with an average moisture content of about 35%; continuous light evaporation reduces the soil moisture content at 20cm, but the ISA blending and copolymerization with the surface soil form a dense structure, which reduces the loss of soil water. With the increase of the amount of curing agent (8%, 10%), the change of moisture content in the bionic soil deviates from the distribution pattern of the natural soil layer: although it is still dominant in terms of absolute value of moisture content, the reduction of soil pores isolates the capillary water siphon distribution in the vertical distribution of the soil, making soil moisture migration difficult.
[0080] Figure 4 b shows the longitudinal moisture content distribution characteristics of soil columns with different curing agent dosages at 1d, 3d, 7d, 15d, 45d and 60d. The total moisture content of all soil columns decreased significantly with the evaporation time. Comparing the soil water loss rate at the depth of 40cm in the soil column during the 60d period, it can be found that the original soil (0%) is 34.79%, while 2%, 4%, 6%, 8% and 10% are 45.07%, 30.30%, 30.96%, 34.73% and 29.16%, respectively, with no significant difference; longitudinally comparing the changes in soil moisture values from 40cm to 60cm, they increased by +12.22%, -0.03%, +25.73%, +0.09%, -0.06% and 0.01%, respectively. It can be found that when the curing agent dosage is greater than 6%, the moisture change in the longitudinal distribution of the soil column is relatively stable, and it meets the requirements of water retention as a reconstructed soil layer for filling gangue gaps. In summary, from the analysis of the results of optimizing soil moisture migration, 6% ISA curing agent dosage is the best choice.
[0081] Example 4: Effects of different bionic soils on the solidification of heavy metals
[0082] The heavy metal leaching in soil was completed according to the method required by China HJ / T 557-2010, and the concentrations of Pb, As, Cu and Zn in soil leaching solution were determined by inductively coupled plasma mass spectrometry (ICP-MS, PerkinElmer Nexlon 300X). The results are shown in Table 6.
[0083] The bionic soil variable pH leaching durability test was designed with reference to US EPA 1316. It is used to verify the anti-erosion ability of bionic soil with different curing agent dosages under different environmental pH. The bionic soil cured to 28 days old was crushed and dried, 40g was weighed through a 2mm sieve, and transferred to a 500mL PVC bottle. Different volumes of 1mol / L KOH and 2mol / L HNO3 were taken to prepare immersion solutions with pH values of 2.0, 4.0, 5.5, 7.0, 8.0, 9.0, 10.5, 12.0 and 13.0 respectively. The solid-liquid ratio was 1:10, the water bath temperature was 25±0.1℃, and it was continuously oscillated for 48 hours at 150±1 times per minute and an amplitude of 40mm. After the oscillation was completed, the PVC bottle was taken out and allowed to stand for 1 hour. 10ml of the supernatant was taken and filtered through a 0.45μm filter membrane. The leaching solution was acidified with HNO3 at a pH of about 2, and the heavy metal test was completed by ICP-MS. The results are shown in Figure 5 .
[0084] Table 6 Heavy metal leaching concentrations of different bionic soils (μg / L)
[0085]
[0086] Table 6 shows the heavy metal leaching values at pH 2, 7 and 12 after the bionic soil was treated with different ISA dosages for 28 days. Because the original soil is not contaminated soil and has a certain heavy metal adsorption capacity, this example only discusses the solidification of exogenous heavy metals by bionic soil. With the addition of ISA, the leaching concentration of heavy metal elements in the bionic soil dropped sharply, among which Pb, Cu and Zn were all less than the groundwater Class II water quality standard specified in GB / T 14848-2017 (Pb 5μg / L, Cu 50μg / L, Zn 500μg / L), and As could also meet the Class IV water quality standard requirements (As 50μg / L). This may be because: a) silicates in PO increase the degree of hydration reaction with increasing dosage or prolonging reaction time; b) hydration reaction and part of Ca(OH)2 dissolved by DG react with Si and Al oxides dissolved in soil minerals and FA to undergo pozzolanic reaction; c) CSH and PAM bond soil particles jointly adsorb heavy metals; d) precipitation and complexation reaction of heavy metal elements. When the ISA dosage is greater than 6%, no Pb is detected in the soil. Some studies have pointed out that the adsorption of Pb by PAM gel can reach 175 mg / g, indicating that Pb is almost completely adsorbed and fixed in the soil in addition to being consumed by the curing agent reaction; the content of Zn is also maintained at an extremely low level, indicating that in extreme acid-base erosion environments, bionic soil also has a good curing and stabilizing effect on Zn. As and Cu elements fluctuate greatly with the increase of curing agent dosage, and their curing and stabilizing effects are further verified by variable pH erosion tests.
[0087] Figure 5 a It can be seen that with the increase of the pH value of the leaching solution, the As concentration shows a trend of first decreasing and then increasing. When the ISA dosage is low (2%), the As fixation effect is weak, which may be because there is not enough solidification reactant generated, and the heavy metal is mainly adsorbed by the soil; when the solidifying agent dosage is greater than 6%, the pH value in the range of 5.5 to 12 is less than the Class II water quality standard requirements, and the lowest concentration occurs at around pH 10. This phenomenon is mainly determined by the stability of heavy metals in the soil: a) Arsenic hydroxides are amphoteric, such as arsenic calcium cuprate PbCu3(AsO4)(OH)2, arsenic lead iron stone (PbFe2(AsO4)2(OH)2) and arsenic calcium cuprate (CaCu(AsO4)(OH)), which are easily dissolved and leached in strong acid and strong alkaline environments, but can form stable hydroxide precipitates in weak alkaline extracts, resulting in lower heavy metal concentrations; b) The hydration products produced by ISA curing agent cross-linking the soil matrix, such as CSH and AFt, are released back into the environment as the pH of the extract decreases; c) The fluctuation of the pH of the extract affects the adsorption capacity of As on the surface of the clay minerals of the bionic soil. Figure 5b It can be seen that as the alkalinity of the leaching solution increases, the leaching concentration of Cu increases accordingly. High pH environment will lead to the hydrolysis of the amide groups in the PAM polymer, forming a large number of negatively charged carboxylic acid groups, which will hydrolyze the gel network structure in the soil and reduce the adsorption capacity of heavy metal elements. Therefore, controlling the ISA dosage and avoiding excessive alkalinization of the bionic soil is one of the important factors to ensure the stability of heavy metals in coal gangue when constructing the bionic soil-coal gangue reconstructed soil layer.
[0088] Example 5: Analysis of pore structure characteristics of different bionic soils
[0089] MIP was performed using a MicroActive AutoPore V 9600 mercury intrusion porosimeter. The pore pressure range was 0-420.29 MPa, and the pore diameter range was 0.003-360 μm. The pore diameter was calculated using the Washburn formula, as shown in formula (4):
[0090]
[0091] where D is the pore diameter of the soil sample (μm), p is the mercury pressure pressed into the soil pores (MPa), γ and Φ are the surface tension coefficient of mercury (N / m) and the contact angle between soil and mercury (°), which are 139° and 4.84×10 -4 N / mm (experimental temperature 25°C).
[0092] The pore peak distribution in the soil sample is fitted by Gaussian distribution function, which has been widely used to evaluate the soil solidification effect. Specifically:
[0093]
[0094] Where n corresponds to the number of peaks in the fitting curve, Vi is the pore volume (mL / g) corresponding to 1g of soil with a diameter of d (μm) in the fitting curve, σi is the standard deviation of the pore volume, and μi is the average pore diameter (μm). The results are shown in Table 7.
[0095] The TG-DSC test was performed under a synchronous thermal analyzer 449F3 (NETZSCH, Germany) to evaluate the thermal stability of bionic soil materials. The dried soil was passed through a 0.075 mm sieve, 10 ± 0.2 mg was taken into a ceramic crucible, and then the sample was heated from 30 °C to 800 °C at a constant rate of 10 °C / min. The experimental atmosphere was nitrogen, and the gas flow rate was 100 mL / min. The results are shown in Figure 6 .
[0096] Table 7 Pore volume distribution of bionic soil with different ISA dosage and curing time
[0097]
[0098] According to Horpibulsuk's classification standard for solidified soil, soil pores are divided into intra-aggregate pores (<0.01μm), inter-aggregate pores (0.01μm~10μm) and air pores (>10μm) with a cut-off value of 40. The results show that when the ISA dosage increases from 2% to 10% (Table 7), the inter-aggregate pores decrease from 0.3326μm to 0.2033μm. It can be seen that the decrease in the total pore volume of bionic soil with time or dosage is mainly due to the reduction in the pore volume between aggregates. Figure 6 b shows the change of pore-size distribution (PSD) in bionic soil, and the y-axis is dV / dlogd, which represents the pore density distribution in soil. It can be found that low ISA dosage (2%, 4%) shows a typical bimodal PSD, which can also be observed in clean clayey soils and slag-stabilized soil. With the increase of curing agent dosage, the bimodal gradually converges to a single peak. It can be seen from the 28d curing age that the 6% bionic soil has a typical bimodal feature ( Figure 6 c), the average soil pore diameters of the fitting curves f1(d) and f2(d) are μ1, 1.24 μm, and μ2, 3.59 μm, corresponding to soil pore volumes of 0.0246 mL·g -1 and 0.0999 mL·g -1 ; The μ and V of 10% bionic soil fitting were reduced to 1.82μm and 0.0544mL·g -1 , which is consistent with the single-peak psd( Figure 6 d), which means that the air pores and inter-cluster pores in the soil pores are filled with reaction products and converted into intra-cluster pores, forming a denser soil pore structure, which is manifested as better mechanical properties in macroscopic terms. However, low permeability will also weaken the ecological performance of the soil and is not conducive to water-gas exchange in the soil. A low-dosage curing agent is a better choice.
[0099] Example 6: Characterization of microstructure characteristics of different bionic soils
[0100] Scanning electron microscopy (SEM, ZEISS Gemini 300) and energy dispersive X-ray spectroscopy (EDS, OXFORD XPLORE30) were used to observe the microstructure and element distribution characteristics of bionic soil prepared with different modified curing agents. Soil samples of the target curing age were selected, freeze-dried, crushed and ground to 200 mesh, adhered to conductive glue, and gold was sprayed for 45s using a Quorum SC7620 sputtering coater with a gold spraying current of 10mA. The accelerating voltage was 3kV for morphological photography, 15kV for energy spectrum photography, and the detector was an SE2 secondary electron detector. The results are shown in Figure 7 and Figure 8 .
[0101] Figure 7 a shows the microstructure of bionic soil at different ISA dosages (curing time 28d). Compared with the flaky structure of the in-situ soil (0%), the low-dosage bionic soil (6%) still retains the original soil morphology due to the low PO content, but a small amount of calcium aluminate can be seen. With the further increase of the curing agent dosage, the hydration products distributed in the silt are more extensive. At 10% dosage, a significant filling effect can be seen in the soil pores, and the inter-aggregate pores are significantly reduced; when the dosage ratio is increased to 30%, the soil surface is covered and filled with a large amount of CSH and CASH gel. At the same time, due to the dissolution and condensation of PAM, the soil particles are connected in a network, making the soil have higher strength and low permeability. When the ISA dosage ratio reaches 60%, the soil shows typical cement soil morphology characteristics, and a large amount of needle-shaped or strip-shaped calcium aluminate grows along the pore wall to fill the original pores between the soil layers. In order to ensure that the modified soil has good water retention and air permeability, high ISA dosage should be avoided, which has been verified in the previous article.
[0102] XRD patterns of in-situ soil and 6% bionic soil at 14d and 28d Figure 7 As shown in b. AFt peaks appeared in the bionic soil, CSH was not detected in the 14-day-old soil, and the diffraction peak of CSH at 28 days was weaker than that of calcium aluminate, which was related to the low content of PO in the bionic soil. There were diffuse halos in the 2θ range of 30° to 37°, indicating the formation of amorphous compounds CASH. This is because in the initial stage of adding water to the bionic soil, the C2S silicon-rich phase in the cement quickly decomposed to generate free Si 4+ , which gradually increases the concentration of H3SiO4- in the soil pore water and hydrolyzes free Ca 2+Combined to generate a certain concentration of CSH (Formula 6). Due to the volcanic ash effect of FA, it can be activated in an alkaline environment. It is also one of the commonly used main materials for the preparation of geopolymers. It is easier to participate in the reaction and insert into the pores of soil particles to make the soil structure more compact. The Al in FA can replace the Si released by PO hydration. 4+ , in a slightly alkaline environment, it is converted into AlO2- to generate H3AlO4 2 - and H3SiO4- structures, interacting to form a gelled network structure (Formula 7). At the same time, because PAM particles are believed to be mainly attached to the voids of the gelled matrix, the hydrophilic polymer has a good binding effect with CSH, which can further benefit soil reinforcement and heavy metal adsorption. Figure 7 c is the EDS element distribution diagram of 6% bionic soil at 28 days of age. It can be seen that heavy metals Cu, Zn, As and Pb are evenly distributed, indicating that PAM gel and ISA hydration products play a role in joint fixation. Combined with XRD, it can be found that helmutwinklerite Pb(Zn,Cu)2(AsO4)2·2H2O is generated at 2θ of 27.3°, which is related to the high content of added exogenous heavy metals. In the actual process of using bionic soil to treat coal gangue for soil reclamation, the leaching amount of heavy metals in the gangue is lower, and the bionic soil will have a better solidification and stabilization effect on the potential heavy metals in the gangue.
[0103] C2S+H2O→CS-H+Ca(OH)2+Ca 2+ +Si 4+ (6)
[0104]
[0105] TG results are as follows Figure 8 As shown in a, the microscopic material structure of bionic soil is further verified. When the ISA content is 6%, the weight loss rate is the highest during the entire heating process, and the total thermal weight loss is the largest, which is 25.28%. This shows that 6% bionic soil has the best water retention rate, which is also verified by the SWCC experiment mentioned above. Combined with the DSC curve ( Figure 8b), a total of 5 obvious endothermic peaks appeared. Due to the incorporation of PAM, the bonding connection of soil particles is improved. The dehydration of the bionic soil within 113°C is mainly free water; when it is actually used for gangue grouting backfill to construct a natural soil layer, it can effectively achieve the flame retardant effect of gangue. 175°C is the dehydration of gel hydration products such as CSH, which is consistent with the observation results of the XRD experiment. 450°C is the dehydration of Ca(OH)2 or the decomposition of kaolin minerals in clay, indicating that the incorporation of ISA has changed the mineral composition of the soil. When the temperature is between 700 and 800°C, the thermal weight loss rate of the bionic soil suddenly increases, corresponding to the decomposition of carbonates such as CaCO3.
[0106] Example 6: Evaluation of the solidification and stabilization effects of different bionic soils and coal gangue
[0107] 1. Preparation of bionic soil-coal gangue solidification samples
[0108] The Bulianta coal gangue was crushed and sieved to a particle size of 1.0-3.0 mm, the ratio of gangue to bionic soil was 7:3, and the water-solid ratio was 0.6, and a bionic soil standard sample (Φ5cm×H 10cm) was prepared. After curing for 90 days, the heavy metal leaching experiment (China HJ 557-2010, pH of the leaching solution = 7) and microscopic morphology test of the test block after the bionic soil solidified the coal gangue were completed. The specific experimental methods are as described above.
[0109] There are two types of bionic soil used above: bionic soil I and bionic soil II:
[0110] Bionic soil I is the bionic soil prepared by Example 1, wherein the ISA content is 6%.
[0111] Bionic soil II is a modified polyacrylamide obtained by modifying the polyacrylamide used on the basis of bionic soil I. The preparation process of the bionic soil II is as follows:
[0112] Preparation of modified polyacrylamide: polyacrylamide (molecular weight of 15 million) is dissolved in water to obtain a polyacrylamide solution with a concentration of 3%, and then monomethacrylate glycerol (the amount added is 2 times the mass of polyacrylamide) and styrene sulfonic acid (the amount added is 1 times the mass of polyacrylamide) are added to the obtained polyacrylamide solution, and ammonium persulfate (the amount added is 0.5% of the total mass of monomethacrylate glycerol and styrene sulfonic acid) is added at the same time to carry out polymerization reaction to obtain modified polyacrylamide.
[0113] The mass ratio of cement, fly ash and desulfurized gypsum in the curing agent ISA is 12:8:3.
[0114] Bionic soil II was prepared according to the method described in Example 1.
[0115] 2. The actual engineering application scenario of bionic soil is: the soil is injected into the cracks of gangue in the form of slurry to construct the bionic soil-gangue soil reconstruction layer as a whole ( Fig. 9 ). In the soil layer constructed by traditional waste rock reclamation, the waste rock is isolated into different units by the covering soil layer. The bionic soil prepared in this study is solidified by grouting and constructed by waste rock to form a whole, and the water migration in the new soil layer is continuous and complete.
[0116] Finally, the geotechnical properties and heavy metal leaching tests were conducted on the bionic soil-gangue soil column (Φ5cm×H 10cm) prepared in the laboratory. The 28-day UCS average of the bionic soil-gangue soil column was 422kPa, which was greater than the 350kPa recommended by the US EPA, indicating that the gangue can further improve the overall geotechnical properties when used as fine aggregate. According to the provisions of GB / T 14848-2017, the Pb, Zn, Cu, As, Hg, Cr, Cd, Ni and Mn elements of bionic soil I-gangue and bionic soil II-gangue samples were evaluated. The leaching values were all less than the requirements of Class III underground water, and the leaching values of each metal of bionic soil II-gangue samples were significantly lower than those of bionic soil I-gangue samples. The results show that the bionic soil II modified by polyacrylamide can further improve the solidification effect on heavy metals and reduce the leaching of heavy metals (Table 8). Combined with the SEM results, it can be seen that the bionic soil covers the surface of the gangue, and the reaction hydration products are directly attached to the gangue and soil particles, which plays a role in adsorbing and fixing the potential heavy metals in the gangue. This shows that the bionic soil can effectively fill the pores between the gangue, isolating most of the air while also achieving a certain flame retardant effect. Therefore, the application of bionic soil has achieved the goal of ecological reclamation and disposal of gangue without potential ecological and environmental risks.
[0117] Bionic soil has been successfully applied to a 40-acre pilot base in the Bulianta mining area of Ordos, treating 130,000m of gangue. 3 At present, the deep soil reconstruction and reclamation has been completed, and the monitoring results of groundwater and surrounding soil environment are similar to those in the laboratory, but long-term monitoring is still needed to determine the flame retardant and heavy metal stabilization effects of gangue. Preliminary tests have shown that the bionic soil prepared by modifying the mining area soil with ISA curing agent and PAM can be used to construct a deep soil layer together with gangue, which is feasible for the in-situ large-scale disposal of gangue.
[0118] Table 8 Heavy metal leaching concentrations in in-situ gangue and bionic soil-gangue soil columns
[0119]
[0120] Note: a The heavy metal leaching value experiment refers to China GB / T 25282-2010; bGroundwater Class III standard China GB / T 14848-2017.
[0121] The present invention prepares a new type of bionic soil by modifying the mining soil with PO, FA, DG and PAM / modified PAM. The soil mechanical properties, water migration function and heavy metal solidification effect evaluation of the bionic soil under different ISA dosages are studied to determine its feasibility of jointly reclaiming and constructing a deep soil layer during the in-situ large-scale disposal of gangue. The main conclusions are as follows:
[0122] (1) The addition of the curing agent ISA improves the geotechnical properties of the in-situ soil. With the increase of ISA dosage and curing time, the unconfined compressive strength of the soil is significantly improved, and the pore volume of the bionic soil is reduced. Peak analysis results show that the compressive strength of the bionic soil with 6% ISA dosage presents a bimodal structure during the 28-day curing period.
[0123] (2) The solidifying agent improves the water retention capacity of the in-situ soil. The SWCC results show that the newly mixed bionic soil with 6% ISA has the highest residual moisture content, and the water evaporation experiment shows that increasing the amount of solidifying agent helps prevent water loss in the soil.
[0124] (3) Bionic soil has a good solidification and stabilization effect on heavy metals Pb, Zn, Cu and As. The solidifying agent reaction products CSH, CASH and AFt can not only fill soil pores and improve soil strength, but also adsorb, encapsulate and fix heavy metals. Bionic soil realizes the resource reclamation and utilization of waste rock and improves the ecological environment of the mining area.
[0125] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A sustainable bionic soil, characterized in that: The bionic soil comprises: silt and a curing agent, wherein the curing agent accounts for 6-8% of the mass of the silt; the curing agent comprises a curing agent I and a curing agent II, wherein the curing agent II accounts for 0-1‰ of the mass of the silt.
2. The sustainable bionic soil according to claim 1, characterized in that: The curing agent I comprises: cement, fly ash and desulfurized gypsum; the mass ratio of the cement, fly ash and desulfurized gypsum is (10-12): (6-10): (1-5).
3. The sustainable bionic soil according to claim 1, characterized in that: The curing agent II is polyacrylamide, and the molecular weight of the polyacrylamide is between 10 and 20 million.
4. A method for preparing sustainable bionic soil according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: S1: preparing curing agent I: drying cement, fly ash and desulfurized gypsum and mixing them evenly according to the proportion; Prepare curing agent II: polyacrylamide, molecular weight of 10 to 20 million; S2: Preparation of bionic soil: First, dissolve curing agent II in water to obtain an aqueous solution of curing agent II, then add silt and curing agent I in sequence, stir evenly to obtain a mixture, and subject the obtained mixture to injection molding, curing and demolding in sequence to obtain a sustainable bionic soil product.
5. The method for preparing sustainable bionic soil according to claim 4, characterized in that: In step S1, the drying conditions are: 80-120°C, time 1-3h.
6. The method for preparing sustainable bionic soil according to claim 4, characterized in that: In step S1, the curing agent II is polyacrylamide, and the molecular weight of the polyacrylamide is between 10 and 20 million.
7. The method for preparing sustainable bionic soil according to claim 4, characterized in that: In step S2, the water is added in an amount with a mass ratio of 1:2 to the silt.
8. The method for preparing sustainable bionic soil according to claim 4, characterized in that: In step S2, the stirring conditions are: rotation speed 57-67 r / min, time 5-15 min.
9. The method for preparing sustainable bionic soil according to claim 4, characterized in that: In step S2, the curing process is: first curing under natural conditions for 20 to 26 hours, and then curing at a temperature of 18 to 22° C. and a humidity of 94 to 96%.
10. Use of the sustainable bionic soil according to any one of claims 1 to 3 in resource reclamation of coal gangue.